The role and effects of using the students’ native language in the early stages of learning a foreign language on students enrolled in the Intensive Intermédiate English I courses at the Foreign Language Department in the University of El Salvador in the year 2015 - Aguilar Archila, Nataly Magdalena; Cortez Castillo, William Antonio; Hernández Miranda, Vicente Javier; Gómez Alegria, Ana Grace; Landaverde Castillo, Manuel Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2016)
Ever since, one decides to become an education professional, there is a commitment for working in pro of the education of those who have trusted us with our guidance towards the learning of foreign languages. It is then, our responsibility to take an active role in the improvement of the quality of education that is provided. Being in a non-English speaking environment, it is our creativity, and determination the one that leads us to help others learn the language. However, we often let ourselves be led by the ideas of those professionals that teach in different environments. Take for example, in the United States, most students come from many different cultural backgrounds including language and traditions. Therefore, instructors must adapt to such conditions. In El Salvador, on the other hand, the use of the students´ common language is often neglected by teachers in order to copy the style of more developed countries, ignoring the fact that we live in a different environment. This is why, this research report, the role and effect of using the students’ native language in the early stages of their learning of English is re-examined in detail. As well as, its effects on students´ learning of the target language.
Incluye anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2016.
Audiencia general.